Pengaruh Kualitas Produk, Layanan Purna Jual dan Jaminan Produk terhadap Kepuasan Pelanggan : (Studi pada Pelanggan PT Karya Bahari Abadi Jakarta) - Reynaldi Syahputra; Rina Ayu Vildayanti (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The problem of the level of consumer trust and satisfaction is important in the trade business. However, not all products that have been and have not been regulated have adequate after-sales service. The purpose of this study was to determine the effect of after-sales service, product quality and product warranty on customer satisfaction. The number of samples in this study amounted to 100 consumers from a population of 180 consumers and are active consumers of PT Karya Bahari Abadi Jakarta. The sampling technique is by accidental sampling. The data collection technique is primary data or data taken directly from the respondents through a questionnaire. This study uses multiple linear regression and comparative analysis for data analysis with the help of SPSS Ver. 21, This study obtained the results that the quality product, after-sales service, product guarantee has a positive effect simultaneously on customer satisfaction, quality product, after-sales service, product guarantee has a partial positive effect on customer satisfaction. Through data processing, researchers can provide input or advice to companies, namely companies are expected to be able to maintain product quality that has been rated well by customers and pay more attention to after-purchase services to create satisfaction which ultimately impacts on customer loyalty.